Investigating the integration of user values with design rationale and its effects on HCI design artifacts - Teixeira, Bianca Rodrigues; Barbosa, Simone D. J. (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
User values are a significant part of designing software, but are not always considered the main focus. When performing decision-making activities, user values can get lost among the designers’ own biases. This work studies the integration of user values with a design rationale technique, namely Questions, Options, and Criteria (QOC), and also how this integration reflects on a resulting design artifact (a MoLIC interaction diagram). We performed two separate studies with Computer Science students in Rio de Janeiro. We found that user values can be integrated into design rationale using different notations, such as highlighting the values (through circling or underlining) stated in the options or criteria. The decisions made with the QOC method using user values did result in relevant impacts on MoLIC diagrams. Participants who designed for a persona with strong values had richer results than those who used a “generic” persona. In a second study, we found that designers can recognize when user values are embedded into design artifacts. These results are encouraging to continue research regarding user values, with possibilities of developing new methods or updating existing techniques and notations such as QOC or MoLIC to support user values.